Study of associations of blood proteins with development of unstable atherosclerotic plaques in coronary arteries by quantitative proteomics - E. M. Stakhneva; E. V. Kashtanova; Ya. V. Polonskaya; E. V. Striukova; V. S. Shramko; E. V. Sadovski; A. V. Kurguzov; I. S. Murashov; A. M. Chernyavskii; Yu. I. Ragino (Бюллетень сибирской медицины, 2023)
Aim. To study the associations of blood proteins with the presence of unstable atherosclerotic plaques in the arteries in patients with coronary artery disease using the quantitative proteomic analysis.Materials and methods. The study included patients with coronary artery disease (n = 40); the average age of patients was 58 ± 7 years. Material for the study was blood serum. Protein concentrations in serum samples were determined using the PeptiQuant Plus Proteomics Kit (Cambridge Isotope Laboratories, USA). Protein fractions were identified using the liquid chromatograph and tandem mass spectrometer Q-TRAP 6500.Results. Mass spectrometry revealed an increased concentration of proteins, such as fibrinogen, fibulin-1, and complement factor H, in the serum samples of patients with unstable atherosclerotic plaques. It took place with a simultaneous decrease in the levels of α 2-antiplasmin, heparin cofactor II, coagulation factor XII, plasminogen, prothrombin, vitronectin, complement proteins (C1, C3, C7, C9), and complement factor B. The differences were considered significant at p < 0.05. It was revealed that the presence of unstable atherosclerotic plaques was associated with the level of fibulin-1 (Exp(B) = 1.008; р = 0.05), plasminogen (Exp(В) = 0.995; р = 0.027), and coagulation factor X (Exp(В) = 0.973; р = 0.037).Conclusion. An increased concentration of fibulin-1 can be considered as a potential biomarker of unstable atherosclerotic plaque development in coronary artery disease. The possibility of using the studied proteins as biomarkers of unstable atherosclerotic plaques requires further studies on their potential role in the development of this disease.